التوحيد عند المعتزلة الجدد: هارون ناسوتيون نموذجا - Hamdan Maghribi (TSAQAFAH, 2018)
The collapse of the Abbasid Dynasty has a major impact to the inﬂuence and presence in the Mu’tazilah school of thought at the time. Mu’tazilah subsequently faded away. Nevertheless, Mu’tazilah’s offer that gives a large portion of reason in understanding the context of revelation and time attracts a lot of contemporary Muslim intellectuals attention. One of them is Harun Nasution who preserves his theological ideology with the Neo-Mu’tazilah, as the successor of the earlier Mu’tazilah. Harun plays an important role in reviving the Mutazilah’s point of view in understanding the religious context, especially in Indonesia. Theological studies of Islam in Indonesia are no more than footnotes from the point of view that Harun and his disciples have disseminated. One conversation that is of great concern among Mu’tazilah and other ‘Ilm al-Kalâm schools of thought is the concept of monotheism, which leads to the discussion about the nature of God, justice, will, and deed of humankind. Harun is inseparable with his Neo-Mu’tazilah from this discussion. Harun does not contradict the classical Mu’tazilah opinion of the concept of Tawhid. The review and analysis of this article use literature review referring to the primary references; classical Mu’tazilah fgures, Neo-Mu’tazilah that Harun has been the voice of, as well as the authoritative literature outside Mu’tazilah as the material of analysis and comparison.